2013
DOI: 10.1007/s00203-013-0936-0
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the role of Burkholderia cenocepacia membrane proteins in antimicrobial properties of chitosan

Abstract: Chitosan, a versatile derivative of chitin, is widely used as an antimicrobial agent either alone or mixed with other natural polymers. Burkholderia cenocepacia is a multidrug-resistant bacteria and difficult to eradicate. Our previous studies shown that chitosan had strong antibacterial activity against B. cenocepacia. In the current study, we have investigated the molecular aspects for the susceptibility of B. cenocepacia in response to chitosan antibacterial activity. We have conducted RNA expression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Chitosan at a concentration of In those cases, effective concentrations of chitosan were 10-100 μg ml −1 (Fang et al, 2010). Activity of chitosan against B. cenocepacia, a multidrug-resistant pathogen that is difficult to eradicate, has also been demonstrated (Ibrahim et al, 2014). Leaving aside human pathogens, the apricot fruit-rot pathogen, B. seminalis, could be eradicated by treatment with chitosan at 2 mg ml −1 (Lou et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chitosan at a concentration of In those cases, effective concentrations of chitosan were 10-100 μg ml −1 (Fang et al, 2010). Activity of chitosan against B. cenocepacia, a multidrug-resistant pathogen that is difficult to eradicate, has also been demonstrated (Ibrahim et al, 2014). Leaving aside human pathogens, the apricot fruit-rot pathogen, B. seminalis, could be eradicated by treatment with chitosan at 2 mg ml −1 (Lou et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Another study on members of the same complex was conducted in sputum from cystic fibrosis (CF) patients in China (Fang et al., ). The third report focused on the multidrug‐resistant B. cenocepacia (Ibrahim et al., ). Chitosan can lethally damage bacterial cell membranes leading to the leakage of proteins, nucleic acids and other intracellular components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, Ch has been demonstrated to inhibit the antimicrobial effect of a metallic nanomaterials, such as ZnNPs (Huh and Kwon 2011). The antimicrobial mode of action Ch NPs is not entirely understood (Ibrahim et al, 2014). Previous studies have indicated disruption of cell membrane functions (proteins inactivation, interfering with respiratory chain, drug efflux system and transport), resulting in membrane lysis and cell death (Bratlie et al, 2012).…”
Section: A Chitosan (Ch Nps)mentioning
confidence: 99%
“…The use of chitosan along with metal nanoparticles is not feasible since chitosan reduced the activity of metal nanoparticles such as Zn. It can be used in combination with antibiotics [76,78]. Even though some studies state that the interaction of cells with chitosan lead to membrane destabilization, followed by lysis and cell death, the detailed mode of action is unclear [79].…”
Section: Chitosanmentioning
confidence: 99%